Profiling of Canonical and Non-Traditional Cytokine Levels in Interferon-β-Treated Relapsing–Remitting-Multiple Sclerosis Patients - D’Angelo, Chiara; Reale, Marcella; Costantini, Erica; Di Nicola, Marta; Porfilio, Italo; de Andrés, Clara; Fernández-Paredes, Lidia; Sánchez-Ramón, Silvia; Pasquali, Livia (Frontiers in Immunology, 2018)
Background: Multiple sclerosis (MS) is a chronic, progressive autoimmune disease of the central nervous system in which inflammation plays a key role in the induction, development and progression. Most of MS patients present with Relapsing-Remitting (RR) form, characterized by flare-ups followed by periods of recovery. Many inflammatory and anti-inflammatory cytokines have been suggested as contributors in MS pathogenesis, and the balance between these opposing cytokines can regulate MS severity. Interferon (IFN)-β, an effective disease modifying therapy for MS, has demonstrated beneficial effects in reducing disease severity in MS patients. However, its immunoregulatory and anti-inflammatory actions in MS are not wholly understood. The aim of the study was to determine, in clinically stable patients with RR-MS, the serum concentration of several cytokines, canonical or not, and their modulation by IFN-β therapy. Methods: RR-MS patients were enrolled and diagnosed according to revised Mc Donald Diagnostic Criteria. A set of cytokines (including non-canonical neurotransmitter ACh and adipokines) and B-cell differentiation molecules, as potential biomarkers were evaluated in 30 non-treated RR-MS patients compared to 30 IFN-β-treated MS patients and 30 age, gender and body mass index-matched healthy controls (HC). Results: Naïve MS patients showed significantly higher levels of IL-1β, IL-12/IL-23p40, IL-18, HMGB-1 and IL-18BP than MS treated patients (p<0.001 for all) and healthy controls (p<0.01). IFN-β therapy has significantly down-modulated IL-1β, IL-12/IL-23p40, IL-18 to normal levels (p<0.001); while it has decreased IL-18BP (p<0.001). Acetylcholine was significantly higher in the IFN-β-treated than HC and non-treated MS patients (p<0.001). No significant differences were observed neither in adipokines concentration or in B-cell associated molecules among the three study groups. Conclusions: Although more experimental evidences are required, we speculate that the efficacy of treatment of MS with IFN-β is mediated, at least in part, by its ability to work on several levels to slow down the disease progression. Proposed actions include the modulation of IL-1-inflammasome axis, and modulation of acetylcholine, BAFF/APRIL system and several adipokines.